Human Resource Analytics in Decision Making Strategic in Modern Education Management - Hendrik Legi; Yoel Giban; Alfred Melkianus Toh; Gideon Widiono (PT. Riset Press International, 2026)
This study aims to analyze the role of Human Resource Analytics (HRA) in strategic decision-making in modern education management and its implications for the effectiveness of educational human resource governance. Digital transformation and the increasing complexity of managing educational institutions require educational organizations to adopt a data-driven approach in decision-making, especially in the aspects of managing educators and education personnel. This research uses a qualitative approach with a library research design. Data was collected through documentation techniques against various relevant scientific literature sources, including journal articles, academic books, proceedings, and research documents related to Human Resource Analytics, strategic human resource management, and modern education management. Data analysis is carried out using qualitative content analysis through the process of reduction, categorization, interpretation, and systematic data synthesis. The results of the study show that Human Resource Analytics plays a strategic instrument in improving the quality of managerial decision-making through the provision of empirical data that supports workforce planning, talent development, performance evaluation, and the formulation of more objective and predictive human resource policies. The implementation of HRA also contributes to improving the efficiency of human resource management, governance transparency, policy accountability, and the adaptive capacity of educational organizations in dealing with changes in the strategic environment. Theoretically, this study strengthens the integration between strategic human resource management approaches and evidence-based educational management in the context of modern education. Practically, this study emphasizes the importance of digital infrastructure readiness, data-driven organizational culture, and the analytical competence of education leaders in supporting the effective implementation of HRA. The findings of the study confirm that Human Resource Analytics is a strategic foundation in the development of an adaptive, professional, and data-based education management system. This study contributes that HRA allows educational institutions to measure the effectiveness of training and professional development programs empirically, so that organizational investment in human resource development can be carried out more efficiently and impactfully.